Внедрение дистанционного обучения в процесс повышения квалификации руководителей учреждений дошкольного образования - Шашок, В. Н. (БНТУ, 2013)
The article explored the possibilities of distance education in the organization of the process of raising preschool managers qualification, evaluated first practical results.
Implementation of distance education in process of raising preschool managers qualification